The Effect of Light Conditions on Photoplethysmographic Image Acquisition Using a Commercial Camera - He Liu; Yadong Wang; Lei Wang (IEEE Journal of Translational Engineering in Health and Medicine, 2014)
Cameras embedded in consumer devices have previously been used as physiological information sensors. The waveform of the photoplethysmographic image (PPGi) signals may be significantly affected by the light spectra and intensity. The purpose of this paper is to evaluate the performance of PPGi waveform acquisition in the red, green, and blue channels using a commercial camera in different light conditions. The system, developed for this paper, comprises of a commercial camera and light sources with varied spectra and intensities. Signals were acquired from the fingertips of 12 healthy subjects. Extensive experiments, using different wavelength lights and white light with variation light intensities, respectively, reported in this paper, showed that almost all light spectra can acquire acceptable pulse rates, but only 470-, 490-, 505-, 590-, 600-, 610-, 625-, and 660-nm wavelength lights showed better performance in PPGi waveform compared with gold standard. With lower light intensity, the light spectra >600 nm still showed better performance. The change in pulse amplitude (ac) and dc amplitude was also investigated with the different light intensity and light spectra. With increasing light intensity, the dc amplitude increased, whereas ac component showed an initial increase followed by a decrease. Most of the subjects achieved their maximum averaging ac output when averaging dc output was in the range from 180 to 220 pixel values (8 b, 255 maximum pixel value). The results suggested that an adaptive solution could be developed to optimize the design of PPGi-based physiological signal acquisition devices in different light conditions.